PENGARUH TRANSPARANSI KEUANGAN PENGELOLAAN ZAKAT, DAN SIKAP BADAN AMIL ZAKAT TERHADAP TINGKAT KEPUASAN MUZAKI DALAM MEMBAYAR ZAKAT DI BAITUL MAAL PROVINSI ACEH (STUDI KASUS : BAITUL MAL ACEH) - Pohan, Zulfikar Riza Hariz; Mutia, Evi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this study was to determine how the effect of transparency of financial reporting, Attitude of Amil Zakah for management of zakat towards the level of trust muzaki. (Case studies on Baitul Mal Aceh). This is study used based on purposive methode, sample of 78 Muzaki in Banda Aceh. The research type used is hypothesis testing research. The data was collected by using questionnaire. The questionnaire were delivered to every Muzaki as sample. The analytical method used is multiple regression analysis with SPSS version 23. The results of this study indicate that; First there is a significant influence on the level of transparency of financial and amil Zakah attitude statements muzakki trust. Secondly, there is a significant influence on the level of Transparency for muzaki who pay zakah. And, very Influence in Amil Zakah Attitude for muzaki trust.